Histone chaperone HIRA regulates adiponectin expression and obesity-associated adipose expansion by facilitating Pol II pause release - Danyang Wan; Ji-Eun Lee; Young-Kwon Park; Guojia Xie; Susanna Maisto; Christabelle Agyapong; Keiko Ozato; Oksana Gavrilova; Kai Ge (Proceedings of the National Academy of Sciences, 2026)
Adipose tissue is essential for maintaining glucose and lipid homeostasis in mammals. However, epigenomic mechanisms underlying adipose tissue function remain largely unclear. Here, we identify the histone chaperone HIRA as an epigenomic regulator of adipose tissue function. Adipose tissue-specific knockout of Hira in mice impairs insulin sensitivity and restrains adipose tissue expansion during high-fat diet-induced obesity. Mechanistically, HIRA is required for the expression of Adipoq , encoding the adipokine adiponectin, and lipid metabolism genes in adipose tissue. Genomic mapping reveals that HIRA binds to promoters and enhancers of Adipoq and lipid metabolism genes in adipocytes. Acute HIRA depletion using the dTAG system, followed by nascent RNA-Seq and ChIP-Seq, demonstrates that while HIRA is largely dispensable for enhancer activation and coactivator binding, it promotes transcription of target genes by facilitating RNA polymerase II pause release and subsequent elongation likely independently of H3.3 deposition. Our findings uncover a mechanism by which HIRA regulates transcription and establish HIRA’s critical role in insulin sensitivity and lipid metabolism, providing a potential therapeutic target for obesity and insulin resistance.